Proximal Myopathy due to m.5835G>A Mutation in Mitochondrial MT-TY Gene. (10th December 2018) - Simoncini, C.; Montano, V.; Alì, G.; Costa, R.; Siciliano, G.; Mancuso, M.
Abstract : Mitochondrial (mt) tRNA (MTT) gene mutations are an important cause of mitochondrial diseases and are associated with a wide range of clinical presentations. Most mutations fall into three mitochondrial tRNAs (tRNAIle, tRNALeu (UUR), and tRNALys) and are responsible for half of the mitochondrial diseasees associated with tRNA mutation, with MERRF, MELAS, mitochondrial myopathy, and Leigh syndrome being the most frequent phenotypes. More than 100 tRNA pathogenetic mutations are described, showing little correlation between the observed clinical phenotype and a specific mitochondrial tRNA mutation. Furthermore different mutation can manifest with similar clinical phenotypes, making the genotype-phenotype correlation difficult. Here we report the case of an Italian 53-year-old woman presenting with a proximal myopathy and the m.5835G>A mutation in MT-TY gene coding for the mitochondrial tRNA Tyrosine gene.